DIPLOMASI KEBUDAYAAN INDONESIA TERHADAP AMERIKA SERIKAT MELALUI KULINER (GASTRODIPLOMACY) TAHUN 2010-2016 - Sarah Minotti Jiun; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Cultural diplomacy is a category of Soft Diplomacy in the implementation of a country's foreign policy. Cultural diplomacy is a manifestation of the implementation of public diplomacy. One of the cultural diplomacy instruments used by Indonesia to United Kingdom in Cultural Festival. Diplomacy through festival is known as Cultural Diplomacy. Indonesian's Festival aims to win the hearts and minds of foreigners thereby increasing interaction and cooperation with other countries. Using the theory of diplomacy is the concept of soft power by Joseph Nye, Jr and perspective of Neorealism by Kenneth Waltz, this research obtained data through literature studies and direct research to the Indonesia Ministry of Foreign Affairs. The research shows that Indonesian's Cultural Diplomacy have been done through annual festivals serving Indonesian culinary, art,and fashion, participation of Indonesian government in annual culinary festival held by the United Kingdom. It was also found that the implementation of culure diplomacy impacts the level of increasing number of tourist from the United Kingdom to visit Indonesia. Keywords: Culture Diplomacy, Public Diplomacy